Targeting of glycoprotein I (gE) of varicella-zoster virus to the trans-Golgi network by an AYRV sequence and an acidic amino acid-rich patch in the cytosolic domain of the molecule. - Zhu, Z (1996)
Previous studies suggested that varicella-zoster virus (VZV) envelope glycoproteins (gps) are selectively transported to the trans-Golgi network (TGN) and that the cytosolic domain of gpI (gE) targets it to the TGN. To identify targeting signals in the gpI cytosolic domain, intracellular protein trafficking was studied in transfected cells expressing chimeric proteins in which a full-length or mutated gpI cytosolic domain was fused to the gpI transmembrane domain and interleukin-2 receptor (tac) ectodomain. Expressed protein was visualized with antibodies to tac. A targeting sequence (AYRV) and a second, acidic amino acid-rich region of the gpI cytosolic domain (putative signal patch) were each sufficient to cause expressed protein to colocalize with TGN markers. This targeting was lost when the tyrosine of the AYRV sequence was replaced with glycine or lysine, when arginine was replaced with glutamic acid, or when valine was substituted with lysine. In contrast, tyrosine could be replaced by phenylalanine and valine could be substituted with leucine. Mutation of alanine to aspartic acid or deletion of alanine abolished TGN targeting. Exposure of transfected cells to antibodies to the tac ectodomain revealed that the TCN targeting of expressed tac-gpI chimeric proteins occurred as a result of selective retrieval from the plasmalemma. These data suggest that the AYRV sequence and a second signaling patch in the cytosolic domain of gpI are responsible for its targeting to the TGN. The observations also support the hypothesis that the TGN plays a critical role in the envelopment of VZV.